Upaya Meningkatkan Kemampuan Guru dalam Menyusun Program Semester Melalui Bimbingan Kelompok di SD Negeri 07 Mancuang Kecamatan Baso - Erma Ariani (Journal on Education, 2022)
This study aims to reveal information and discuss the Efforts to Improve Teacher Ability in Developing Semester Programs through Group Guidance at SD Negeri 07 Mancuang, Baso sub-district. The type of research carried out is School Action Research. The research was conducted at SD Negeri 07 Mancuang, Agam Regency. This research was conducted in the Odd Semester of the 2021/2022 Academic Year, starting in July 2021. The research subjects were 8 academic teachers for the 2021/2022 academic year. The research procedure consisted of two cycles with four stages of research starting from planning, implementing, observing and reflecting. Data collection techniques using instruments and teacher worksheets. The collected data were analyzed using the percentage formula. The results showed that in the first cycle, 37.5% of teachers were able to fill in completely/perfectly. Meanwhile, 62.5% of teachers have not been able to complete the LKG completely/perfectly. obtained 87.5% of teachers who are able to fill in completely/perfectly. Meanwhile, 12.5% ​​of teachers have not been able to complete the LKG completely/perfectly. Based on the results of the research described above, it can be concluded that through group guidance, teachers can improve the ability of teachers in preparing semester programs at SDN 07 Mancuang.